The Influence of Knowledge Sharing, Organizational Agility, and IT Governance on the Digital Innovation Capability of E-Commerce Companies - Djunaedi, Djunaedi; Hendratni, Tyahya Whisnu; Ahmad, Ahmad; Haribowo, Rio; Sidjabat, Sonya; Apramilda, Riesna (Journal of Information System, Technology and Engineering, 2025)
The objective of this research is to evaluate how knowledge sharing, organizational agility, and IT governance impact the digital innovation capability of e-commerce firms in Indonesia. The ever-evolving digital technology landscape demands quick and precise innovation capabilities from e-commerce companies to remain in the race and meet the customers’ wants. In this research, the quantitative method is applied through a survey of 200 respondents that are mainly from the national-scale e-commerce companies and digital startups. The outcomes indicate that all the three independent variables positively and significantly influence the capability of digital innovation. Knowledge sharing stimulates the cooperation of employees innovatively, the agility of an organization speeds up its adaptation to changes in the digital market, and IT governance takes care that the strategic way of innovation is both controlled and efficient. This study, besides being a theoretical contribution to organizational resource-based digital innovation management literature, has also practically benefited e-commerce firms through advising them to apply knowledge sharing strategies, organizational agility, and IT governance to strengthen their digital innovation competencies.